Aerobic Exercise Improves Physique and Quality of Life in Breast Cancer Patients During Anthracycline-based Chemotherapy: a Randomized Controlled Trial - LI Hongmei, ZHANG Yimin, WANG Yong, ZHANG Yurong, JIA Xiao, YU Jingjing, SANG Die (Zhongguo quanke yixue, 2025)
Background Anthracyclines are fundamental in the chemotherapy treatment of breast cancer, but these treatments often lead to changes in physique, such as increased body fat and decreased cardiopulmonary function, alongside gastrointestinal reactions and bone marrow suppression, thereby impacting the patients' quality of life. Current studies on the ameliorative effects of exercise on these side effects yield inconsistent results, necessitating further research. Clinically, the efficacy and safety of exercise prescriptions in mitigating these chemotherapy side effects in breast cancer patients warrant further exploration. Objective This study aims to investigate the effectiveness and safety of aerobic exercise in improving the physique and quality of life of breast cancer patients during anthracycline-based chemotherapy. Methods This study is a randomized controlled trial involving 44 adult female breast cancer patients who received anthracycline-based chemotherapy at Beijing Chaoyang Sanhuan Cancer Hospital, from March 2022 to January 2023. They were randomly assigned to an exercise group (23 participants) and a control group (21 participants). The control group was informed about personalized exercise guidance after chemotherapy. The exercise group, under the supervision of rehabilitation therapists, engaged in workouts during their hospital stay and continued personalized exercise interventions at home with self-monitoring and remote supervision by researchers. Key outcome measures, including physique and quality of life, were collected before and after chemotherapy, along with the incidence and severity of gastrointestinal reactions, bone marrow suppression, and exercise-related adverse events. Covariance analysis, using pre-chemotherapy data as covariates, compared the physique and quality of life between the two groups. Results Four participants were lost during the intervention and follow-up, leaving 40 participants (21 in the exercise group, 19 in the control group). No severe adverse events were observed during the exercise intervention. The average compliance with the exercise intervention was 81.8%; average compliance per exercise session was 91.9%, and average compliance with exercise intensity was 92.5%. Post-chemotherapy, the exercise group showed lower body fat weight, body fat percentage, visceral fat area, waist circumference, waist-to-hip ratio, and significantly higher grip strength of the dominant hand and relative peak oxygen uptake (VO2peak) compared to the control group (P<0.05). The incidence of functional impairments post-chemotherapy in the exercise group (7/20) was significantly lower than in the control group (12/16) (χ2=5.707, P=0.017). Post-chemotherapy, the exercise group reported significantly lower scores in physical condition, emotional condition, and additional scores, and higher functional condition scores than the control group (P<0.05). Post-chemotherapy, the control group's physical condition scores (P<0.001) and the exercise group's functional condition scores (P=0.017) were higher than pre-chemotherapy. The control and exercise groups underwent 84 and 94 anthracycline chemotherapy sessions, respectively, with the control group experiencing 84 gastrointestinal reactions and 71 bone marrow suppressions, and the exercise group experiencing 54 gastrointestinal reactions and 45 bone marrow suppressions, showing statistically significant differences between the groups (P<0.05) . Conclusion Aerobic exercise during anthracycline chemotherapy can improve the physique and quality of life of breast cancer patients and is safe when supervised.